2017
DOI: 10.5964/ejcop.v6i1.130
|View full text |Cite
|
Sign up to set email alerts
|

Women as counselling and psychotherapy clients: Researching the therapeutic relationship

Abstract: The present study explores women clients’ experiences of the therapeutic relationship and their meaning making of the effective therapeutic dyad. The participants of the study were 27 female psychotherapy and counselling clients. Individual, semi-structured interviews were conducted and the data was analysed with the use of Interpretative Phenomenological Analysis. The findings indicated: (a) women clients’ attempt to define their relationship with their counsellor by comparing it to other interpersonal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…Frequently, the therapist may see the need to understand his or her own feelings and use this as a tool in the therapeutic interaction; this may improve professional and personal growth when understanding is clear (De La Torre et al., 2005). Moreover, a qualitative study conducted on 27 female clients using interpretative phenomenological analysis (IPA) suggested that women attempted to define their relationship with their counsellor by comparing it to other interpersonal relationships; that is, friendship or family relationships (Kastrani et al., 2017). Furthermore, Kuutmann and Hilsenroth (2012) studied 76 outpatients receiving psychodynamic psychotherapy using a multi‐method evaluation procedure; they discovered that focusing on the patient–therapist interaction in sessions was successful when working with patients who had relational issues.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, the therapist may see the need to understand his or her own feelings and use this as a tool in the therapeutic interaction; this may improve professional and personal growth when understanding is clear (De La Torre et al., 2005). Moreover, a qualitative study conducted on 27 female clients using interpretative phenomenological analysis (IPA) suggested that women attempted to define their relationship with their counsellor by comparing it to other interpersonal relationships; that is, friendship or family relationships (Kastrani et al., 2017). Furthermore, Kuutmann and Hilsenroth (2012) studied 76 outpatients receiving psychodynamic psychotherapy using a multi‐method evaluation procedure; they discovered that focusing on the patient–therapist interaction in sessions was successful when working with patients who had relational issues.…”
Section: Introductionmentioning
confidence: 99%
“…Αντίθετα, ισχυρίστηκαν ότι με άνδρες θεραπευτές χαίρονταν τη διαφορετική τους οπτική, την πιο φιλελεύθερη στάση τους σε σχέση με τους υπόλοιπους άνδρες, αλλά και ότι ταυτόχρονα προβληματίζονταν για την πιθανότητα ερωτικής έλξης μεταξύ τους. Σε άλλη περίπτωση, οι γυναίκες που "εργάζονταν" με γυναίκες θεραπεύτριες παρομοίασαν τη θεραπευτική τους σχέση με μια φιλική σχέση, ενώ οι γυναίκες που εργάζονταν με άνδρες θεραπευτές δήλωσαν ότι μοιάζει περισσότερο με τη γονεϊκή σχέση (Kastrani et al, 2017).…”
unclassified
“…Κατ' αρχάς, οι άνδρες και οι γυναίκες επικοινωνούν με τους ομόφυλους φίλους τους με διαφορετικό τρόπο. Οι γυναίκες φίλες εμπλέκονται σε συζητήσεις, που αφορούν τον εαυτό τους, τη φιλία τους και τις σχέσεις τους με τους άλλους, εκφράζουν τα συναισθήματά τους άμεσα (Kastrani, Deliyanni-Kouimtzis, & Athanasiades, 2017. Χρηστάκης & Χαλάτσης, 2010 και αναφέρουν υψηλότερα επίπεδα συναισθηματικής εμπλοκής, εγγύτητας, ασφάλειας και αυτοαποκάλυψης στις ομόφυλες φιλίες τους από τους άνδρες (Bagwell, Bender, Andreassi, Kinoshita, Montarello, & Muller, 2005).…”
Section: θετικότητα κι ευγνωμοσύνη σύμφωνα με τη θεωρία διεύρυνσης καιunclassified